Metabolic dysfunction and obesity‐related cancer: Beyond obesity and metabolic syndrome. Issue 7 (3rd July 2022) - Karra, Prasoona; Winn, Maci; Pauleck, Svenja; Bulsiewicz‐Jacobsen, Alicja; Peterson, Lacie; Coletta, Adriana; Doherty, Jennifer; Ulrich, Cornelia M.; Summers, Scott A.; Gunter, Marc; Hardikar, Sheetal; Playdon, Mary C.
Abstract: Objectives: The metabolic dysfunction driven by obesity, including hyperglycemia and dyslipidemia, increases risk for developing at least 13 cancer types. The concept of "metabolic dysfunction" is often defined by meeting various combinations of criteria for metabolic syndrome. However, the lack of a unified definition of metabolic dysfunction makes it difficult to compare findings across studies. This review summarizes 129 studies that evaluated variable definitions of metabolic dysfunction in relation to obesity‐related cancer risk and mortality after a cancer diagnosis. Strategies for metabolic dysfunction management are also discussed. Methods: A comprehensive search of relevant publications in MEDLINE (PubMed) and Google Scholar with review of references was conducted. Results: Metabolic dysfunction, defined as metabolic syndrome diagnosis or any number of metabolic syndrome criteria out of clinical range, inflammatory biomarkers, or markers of metabolic organ function, has been associated with risk for, and mortality from, colorectal, pancreatic, postmenopausal breast, and bladder cancers. Metabolic dysfunction associations with breast and colorectal cancer risk have been observed independently of BMI, with increased risk in individuals with metabolically unhealthy normal weight or overweight/obesity compared with metabolically healthy normal weight. Conclusion: Metabolic dysfunction is a key risk factor for obesity‐related cancer, regardless of obesity status. Nonetheless, a harmonized definition of metabolic dysfunction will further clarify the magnitude of the relationship across cancer types, enable better comparisons across studies, and further guide criteria for obesity‐related cancer risk stratification.